Rancang Bangun Sistem Informasi Lokasi Meja Pada Food Court Menggunakan RFID (Radio Frequency Identification) Berbasis Aplikasi Android - Hastuti, Sri (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2020)
Abstrack- Food court locations are placed in current visited places and usually many customer tables that are widely scattered there. It can be too slowly and inefficient ordering, both in terms of time and the process of delivering order because of difficulty of finding a customer table. Based on the explanation above, the authors make a design and build a table location information system in the food court using RFID based android applications. This system allows customers to inform the location of the table to food vendors using RFID. In designing hardware devices, a NodeMCU ESP8266 microcontroller is needed and for designing android software applications using APP Inventor. Google Firebase's realtime database platform was chosen to connect hardware and software devices. The measurement results from the design of this system show that the system is capable of producing precise RFID reading output with an accuracy level of 100% according to the location of the buyer's table. Meanwhile, the average delay obtained from this system is 0.81 seconds. This tool can read the RFID card without a barrier as far as 4.1 cm and cannot read the card if blocked by a metal material.Â Keywords: Food Court, RFID, NodeMCU ESP8266, App Invetor2, FirebaseÂ